Intravenous Anesthesia in Treatment of Nonconvulsive Status Epilepticus: Characteristics and Outcomes - Uysal, Utku (Epilepsy Res, 2015)
OBJECTIVE: To determine factors associated with continuous anesthetic drug (IVAD) use in nonconvulsive status epilepticus (NCSE). METHODS: Retrospective cohort study of patients who met clinical and EEG criteria of NCSE from 2009 to 2014 at a tertiary academic medical center. Patients were categorized according to IVAD use. Outcome variables were response to treatment and in-hospital death. We used descriptive analyses for baseline characteristics and outcome variable differences among patients who did and did not receive IVAD. RESULTS: Forty-three patients had a total of 45 NCSE episodes. IVAD was used in 69% of the episodes. Patients treated with IVAD were younger (53.1±14.1 vs 64.1±13.3, p=0.019). The episodes treated with IVAD occurred more frequently in patients with an acute neurologic pathology (58% vs 21%, p=0.024) and those presenting in a coma (39% vs 7%, p=0.030). NCSE resolved in 74% of the patients who received IVAD. Duration of NCSE did not differ significantly by treatment group. There were total 13 in-hospital deaths: ten in IVAD users vs three in the no-IVAD group (p > 0.05). Only one in-hospital death appeared to be a direct consequence of IVAD use. Mortality was more common among episodes that were not treated according to the published status epilepticus treatment guidelines compared to the episodes where guidelines were followed. CONCLUSION: Our findings showed that factors such as younger age, acute neurologic pathology and coma at presentation were associated with IVAD use in patients with NCSE. These factors should be controlled in the future outcome and effectiveness studies to determine the effect of IVAD use on outcome of NCSE.